Heavy bio‐oils as bio‐binders for rice husk densification: Parameter optimization, binding mechanisms and subsequent pyrolysis and combustion performances. (12th April 2022) - Li, Hui; Yan, Shanshan; Song, Bing; Hall, Peter; Karnowo, Karnowo; Gao, Wenran; Zhang, Hong; Hu, Xun; Zhang, Shu
Abstract: Densification is widely considered as a means to improve the bulk energy density and transportation efficiency of biomass, while the durability and fuel quality of densified biomass often need to be further improved by the addition of binders. In this study, the heavy fractions of bio‐oils from slow pyrolysis (HBO‐SP) and hydrothermal treatment (HBO‐HT) of rice husk (RH) are used as bio‐binders for RH densification. Optimal parameters are determined based on Taguchi methods. They are: densification temperature 130 °C, densification pressure 200 MPa, bio‐binder content 8%, particle size 0.4–0.6 mm, and using HBO‐HT as the binder. The obtained pellets showed a high drop resistance of 99.8% and the binding mechanism is governed by solid bridges between particles. Heavy bio‐oils are deformed and re‐solidified and function as a binder for RH densification. The RH/HBO‐HT pellets showed lower activation energy for pyrolysis as well as lower ignition temperature (292.81 °C compared with 298.34 °C for RH pellets). The higher heating value of pellets was increased from 14.99 to 16.29 MJ kg −1 with 8 wt% HBO‐HT. The co‐densification of heavy bio‐oils and RH provides an approach for producing more qualified solid biofuels from agriculture wastes. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd